2021
DOI: 10.1007/s10389-021-01653-4
|View full text |Cite
|
Sign up to set email alerts
|

Making Every Contact Count and Healthy Conversation Skills as very brief or brief behaviour change interventions: a scoping review

Abstract: Aim To identify and map the available evidence regarding the implementation of Making Every Contact Count and/or Healthy Conversation Skills for both staff delivering and service users receiving the brief or very brief intervention/s. Methods A scoping review approach was used to rapidly map and provide an overview of the relevant literature, identify gaps in knowledge, and inform further, related research. Articles investigating experiences, perceptions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
(219 reference statements)
0
8
0
Order By: Relevance
“…It was also reported that there was a lack of training on the delivery of opportunistic health behaviour change intervention during the pandemic; a finding that is consistent with previous research (Keyworth et al, 2020a). There is a growing body of literature showing that training on opportunistic health behaviour change interventions, such as on MECC or Healthy Conversation Skills, are effective in terms of increasing HCPs' confidence to give and competence to discuss opportunistic health behaviour change interventions (Chisholm et al, 2019; Lawrence et al, 2016, 2020; Parchment et al, 2021). To recover this expertise within the health service, organizations will need to invest in, and deliver, training on opportunistic health behaviour change intervention which target confidence‐building.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that there was a lack of training on the delivery of opportunistic health behaviour change intervention during the pandemic; a finding that is consistent with previous research (Keyworth et al, 2020a). There is a growing body of literature showing that training on opportunistic health behaviour change interventions, such as on MECC or Healthy Conversation Skills, are effective in terms of increasing HCPs' confidence to give and competence to discuss opportunistic health behaviour change interventions (Chisholm et al, 2019; Lawrence et al, 2016, 2020; Parchment et al, 2021). To recover this expertise within the health service, organizations will need to invest in, and deliver, training on opportunistic health behaviour change intervention which target confidence‐building.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pharmacists used innovative ways to engage with patients during mandatory post-vaccination wait. While many of the findings, such as a lack of time and workload pressures, are echoed in the literature as barriers to the implementation of opportunistic health behaviour change interventions pre-pandemic (Keyworth et al, 2019(Keyworth et al, , 2020bParchment et al, 2021), the current results add to the evidence that the health service overall, in its response to the pandemic, became less holistic and patient-centred (Curnow et al, 2021). Thus, it is paramount that the NHS is equipped with the resources and tools to ensure that the prevention and management of long-term health conditions is a focus of routine healthcare consultations in the months to come.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Following the “make every contact count” [ 48 ] principle, we tried to promote behavior at every opportunity. This strategy resulted in more than 40,000 clicks on the vaccination booking system link between 20 August and 17 September 2021.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Queensland's implementation of a stand‐alone Aboriginal and Torres Strait Islander brief intervention program, in the United Kingdom, the Making Every Contact Count approach was applied across all health and social care organisations to embed chronic disease prevention into everyday practice 51 . Lead organisations signed a consensus statement to work together to maximise support for population behaviour change, and help individuals and communities significantly reduce their risk of disease 52 .…”
Section: Discussionmentioning
confidence: 99%